Kajian Prakiraan Penyeberangan Lintas Merak-Bakauheni Berdasarkan Fluktuasi Angkutan - Mulyahadi, Mulyahadi (Warta Penelitian Perhubungan, 2010)
Production of femJ transport Merak-Bakauheni from year to year has increased, especially for autonwbiles-4, but for lowering the passenger experience related to government polia; in 2005, which isto charge on both passenger and goods z:ehicles not subject to tariffs.77te problem faced btj Merak - Bakaulteni todm; is the absence of data based on fluctuations in freightrem; transport at peak and off peak. Fluctuations in transport arrangements will lun:e an impact onfemJ scltedule arrangement, number and mpnci~/ of n.ssels, number of dermnga and parking area 4-wheeled nwtor z:ehicle prmiided.77re metlwd used in forecasting tlrere are two, tire first nwdel I was multi regression and a lineartrend. The forecasting results on Merak femJ - Bakaulreni to 2050 wlten the peak for 4-wheeled nwtorvehicle, namely in the Model I = 3.2 million units and Trend = 3 million units and to BakauheniModel I= 3.55 million units dan Trend= 3.5 million unitsKey Words: Peramalan angkutnn penyeberangnn"